Pathogenetic role and clinical significance of interleukin‐1β in cancer. Issue 2 (7th May 2022) - Malkova, Anna M.; Gubal, Anna R.; Petrova, Anastasia L.; Voronov, Elena; Apte, Ron N.; Semenov, Konstantin N.; Sharoyko, Vladimir V.
Abstract: In recent years, pro‐oncogenic mechanisms of the tumour microenvironment (ТМЕ) have been actively discussed. One of the main cytokines of the TМЕ is interleukin‐1 beta (IL‐1β), which exhibits proinflammatory properties. Some studies have shown an association between an increase in IL‐1β levels and tumour progression. The purpose of this review is to analyse the pathogenic mechanisms induced by IL‐1β in the TМЕ, as well as the diagnostic significance of the presence of IL‐1β in patients with cancer and the efficacy of treatment with IL‐1β inhibitors. According to the literature, IL‐1β can induce an increase in tumour angiogenesis due to its effects on the differentiation of epithelial cells, pro‐angiogenic molecule secretion and expression of adhesion molecules, thus increasing tumour growth and metastasis. IL‐1β is also involved in the suppression of anti‐tumour immune responses. The expression and secretion of IL‐1β has been noted in various types of tumours. In some clinical studies, an elevated level of IL‐1β was found to be associated with low efficacy of anti‐cancer therapy and a poor prognosis. In most experimental and clinical studies, the use of IL‐1β inhibitors contributed to a decrease in tumour mass and an increase in the response to anti‐tumour drugs. Abstract : Scheme of possible mechanisms of regulation of oncogenesis by IL‐1β. The presence of external or tumor antigens may contribute to the development of chronic inflammation with elevated IL‐1β production. High levels of IL‐1β induce canonical and noncanonical pathways in various cells leading to a change in their function. Thus, IL‐1β induces synthesis of proliferative and anti‐apoptotic proteins in epithelial cells (appearance of atypical cells ‐ pretumor), different pro‐angiogenic factors in endothelial cells and contributes to an alteration of differentiation of immune cells in immune suppressive types.